Pengaruh Macam Komposisi Media Tanam Dan Konsentrasi Zat Pengatur Tumbuh Rootone-F Terhadap Pertumbuhan Stek Kembang Kertas (Bougainvillea glabra) Dan Hasil Panen - Bayu Risbarkah, Euis; Komariah, Ai; Mulyana, Hudaya (Fakultas Pertanian Universitas Winaya Mukti, 2024)
This research aims to see whether there is an interaction between the composition of the planting media and the concentration of ZPT Rootone-F on the growth of Bougainvillea glabra cuttings. The results of this research can provide information regarding the composition of the planting media and the concentration of ZPT Rootone-F which can increase the growth of Bougainvillea glabra cuttings. This experiment used a two-factor randomized block design (RAK) and was repeated twice. Factor 1 or more precisely the composition of the planting medium (m) includes 4 levels: m1 = soil + sand + organic fertilizer (1: 1: 1), m2 = soil + sand + compost (2: 1: 1), m3 = soil + sand + compost (1: 2: 1) and m4 = soil + sand + compost (1: 1: 2). The second factor is the use of different concentrations of Rootone-F, including 5 levels: f0 (0 g L-1 Water “Control”), f1 (10 g L-1 Water), f2 ( 20 g L-1 Water), f3 ( 300 g L-1 Water) and f4 (40 g L-1 Water). Differences in media components and Rootone-F concentrations in Bougainvillea glabra cuttings had no effect on the growth of Bougainvillea glabra cuttings. However, they produced different growth independently based on different treatments. Key words: Substances, cuttings, Rootone-F auxin concentration